Avaliando formação de conceito em treinos de múltiplos exemplares com acordes musicais - Átila Moreira Cedro (2018)
Evaluating a teaching procedure based on Multiple Exemplar Training (MET) to establish conditional relations between musical chords and printed words was the first aim in this experiment. In addition, generalization tests were given to participants to evaluate abstraction processes related to different kinds of musical chords (i.e., major, minor, consonant and dissonant chords). Forty college students were equally divided into two groups. Group 1 has been taught about conditional relations between major and minor chords composed by different notes and the printed words "MAIOR" and "MENOR". Group 2, in turn, has been taught about conditional relations between consonant and dissonant chords also composed by different notes and the printed words “CONSONANTE” and “DISSONANTE”. Generalization tests were inserted between each training phase. Five participants from Group 1 and seven participants from Group 2 achieved the learning criteria for all training phases and some of them achieved 100% of correct choices in the generalization tests. By means of statistical tests (T-Test), it was possible to observe that the average of the correct answers in the last generalization test was higher when compared to the average of the correct answers in the Pre-test for participants in both groups. In general terms, our findings suggest that the MET procedure was able to establish conditional relations between musical chords and printed words. Moreover, abstraction processes were observed through the results in the generalization tests.